Organic spectroscopy - Brown, D. W.; Floyd, A. J.; Saninsbury, M. (New York: John Wiley & Sons, 1988)
The availability of modern spectroscopic methods has greatly reduced the need for traditional techniques of structure determination. No longer is it necessary selectively to degrade an organic molecule into smaller recognisable fragments and then attempt to reconstitute the parent structure from them. Nowadays the data obtained from the intact molecule can frequently be interpreted within a few hours to define not only the whole structure but also the details of its stereochemistry. In this book the four techniques most commonly used by organic chemists are introduced and explained. While each has its limitations, together these methods combine to form such an impressive weapon that even very complex structures can be unravelled without recourse to X-ray crystallography. The book is not designed to provide a detailed account of instrumentation or theory of the techniques presented; however, a bibliography is provided for those readers wishing to pursue any of these areas further.
Index 247-250p.
Keywords: Organic; Spectroscopy; Chemistry